Lattice Oxygen Redox Dynamics in Zeolite‐Encapsulated CsPbBr3 Perovskite OER Electrocatalysts - Xiangrong Ren; Yiyue Zhai; Na Yang; Bolun Wang; Shengzhong (Frank) Liu (Advanced Science)
Abstract Understanding the oxygen evolution reaction (OER) mechanism is pivotal for improving the overall efficiency of water electrolysis. Despite methylammonium lead halide perovskites (MAPbX3) have shown promising OER performance due to their soft‐lattice nature that allows lattice‐oxygen oxidation of active α‐PbO2 layer surface, the role of A‐site MA or X‐site elements in the electrochemical reconstruction and OER mechanisms has yet to be explored. Here, it is demonstrated that the OER mechanism of perovskite@zeolite composites is intrinsically dominated by the A‐site group of lead‐halide perovskites, while the type of X‐site halogen is crucial for the reconstruction kinetics of the composites. Using CsPbBrxI3‐x@AlPO‐5 (x = 0, 1, 2, 3) as a model OER catalyst, it is found that the CsPbBr3@AlPO‐5 behaves oxygen‐intercalation pseudocapacitance during surface restructuring due to absence of halogen‐ion migration and phase separation in the CsPbBr3, achieving a larger diffusion rate of OH− within the core‐shell structure. Moreover, distinct from the single‐metal‐site mechanism of MAPbBr3@AlPO‐5, experimental and theoretical investigations reveal that the soft lattice nature of CsPbBr3 triggers the oxygen‐vacancy‐site mechanism via the CsPbBr3/α‐PbO2 interface, resulting in excellent OER performance. Owing to the variety and easy tailoring of lead‐halide perovskite compositions, these findings pave a way for the development of novel perovskite@zeolite type catalysts for efficient oxygen electrocatalysis.